Angiostrongylus costaricensis and the intermediate hosts: observations on elimination of L3 in the mucus and inoculation of L1 through the tegument of mollucs - Bonetti,Vera Cristina Brandão Diniz de Oliveira (1998)
Human accidental infection with Angiostrongylus costaricensis may result in abdominal disease of varied severity. Slugs from the Veronicellidae family are the main intermediate hosts for this parasitic nematode of rodents. Phyllocaulis variegatus, Phyllocaulis soleiformis and Phyllocaulis boraceiensis were experimentally infected to describe the kinetics of L3 elimination in the mucus secretions of those veronicelid species. A maximum of 2 L3/g/day was found in the mucus, while the number of L3 isolated from the fibromuscular tissues varied from 14 to 448. Productive infection was established by inoculations in the hyponotum or in the body cavity, through the tegument. Intra-cavity injection is a less complex procedure and permits a better control of inocula. A preliminary trial to titrate the infective dosis for P. variegatus indicated that inocula should range between 1000 and 5000 L1. The data also confirmed the importance of P. variegatus as an intermediate host of A. costaricensis.